2012
DOI: 10.3109/19401736.2011.643879
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome of the mudskipperBoleophthalmus pectinirostris(Perciformes, Gobiidae): Repetitive sequences in the control region

Abstract: The mudskipper, Boleophthalmus pectinirostris (Perciformes, Gobiidae), is an amphibious gobioid fish. In this paper, the complete mitochondrial genome of B. pectinirostris was firstly determined. The mitogenome (17,111 bp) comprises 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes and 1 putative control region. 130-bp tandem repeat was identified in the control region, which was almost identical among the 10 individuals examined, and three different frequencies of the repeat unit (five, six or seven) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Periophthalmus magnuspinnatus used TAG, TAA and T, but P. modestus preferred TAA, TA and T. The content A þ T was 55.6% and 55.4% for P. modestus and P. magnuspinnatus, respectively. The phenomenon of A þ T content higher than G þ C content was similar to those of B. pectinirostris (Liu et al 2012) and Odontobutis potamophila (Li & Liu 2016). Analysis showed that ND4 and ND5 had the largest number of mutation loci, indicating that they would be better molecular markers than Cyt b gene in examining intraspecific population genetic diversity such as P. magnuspinnatus and P. modestus.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…Periophthalmus magnuspinnatus used TAG, TAA and T, but P. modestus preferred TAA, TA and T. The content A þ T was 55.6% and 55.4% for P. modestus and P. magnuspinnatus, respectively. The phenomenon of A þ T content higher than G þ C content was similar to those of B. pectinirostris (Liu et al 2012) and Odontobutis potamophila (Li & Liu 2016). Analysis showed that ND4 and ND5 had the largest number of mutation loci, indicating that they would be better molecular markers than Cyt b gene in examining intraspecific population genetic diversity such as P. magnuspinnatus and P. modestus.…”
mentioning
confidence: 59%
“…The genomic DNA was extracted from pectoral fin using phenol/chloroform procedure (Sambrook & Russell, 2001). Primers were designed according to Boleophthalmus pectinirostris (Liu et al 2012). Then we used DNA baser V.3.5.4 to assemble the whole sequence.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We found one termination-associated sequence (TAS) and two conserved sequence block (CSB1 and CSB2) domains in S. gigas, while three conserved sequence block (CSB1, CSB2, and CSB3) domains were found in other fish (Sbisà et al, 1997;Walberg & Clayton, 1981) in the control region, which indicates that the two domains (CSB1 and CSB2) are more conserved than the domain (CSB3) in fishes. We did not find the 131-bp tandem repeat which is found in the Boleophthalmus boddarti (Perciformes, Gobiidae) and Boleophthalmus pectinirostris (Perciformes, Gobiidae) (Liu et al, 2012;Zhang et al, 2014), probably because the control region varies between fishes and this tandem repeat region may be lost due to gene mutation in some fishes.…”
mentioning
confidence: 61%
“…This region should be the origin of L-strand replication (OL) in S. gigas, as in most vertebrates (Zardoya et al, 1995). The 22 tRNA genes were identified by the online software tRNAScan-SE 1.21 (Lowe & Eddy, 1997) except the tRNA Ser gene that lacks a dihydrouridine arm, which is common among fishes (Chang et al, 2013a,b;Jin et al, 2013;Liu et al, 2012). The control region was located between tRNA Pro and tRNA Phe genes.…”
mentioning
confidence: 99%